Etika Komunikasi Politik pada pemilihan Umum Terkait Hoax Tahun 2024 - Rifqi Andhy Mahardhika; Muhammad Rafli (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The widespread spread of hoaxes and disinformation across various social media platforms has led to polarization, decreased public trust in political institutions, and clouded voter rationality. This study aims to analyze the practice of political communication ethics during the 2024 election campaign, focusing on how political actors, the media, and the public produce and respond to potentially misleading information. A qualitative approach was used with literature review and discourse analysis methods on political communication content in online media. The findings indicate that weak digital literacy, short-term electoral interests, and insufficient enforcement of regulations are key factors exacerbating unethical political communication practices. Therefore, strengthening political communication ethics through media literacy education, transparency of information from election organizing bodies, and moral commitment from political actors is essential to safeguard the integrity of democracy. The impact of unethical political communication is significant, including increased social polarization, decreased public trust in the democratic process, and the erosion of moral values in the public sphere. To address these issues, the strengthening of political communication ethics through media literacy education for the public, the enforcement of strict regulations on the spread of false information, and moral commitment from political actors and the media are necessary to uphold the integrity of democracy. Thus, political communication ethics should not only serve as a moral guideline but also as a crucial instrument in building a healthy, rational, and civilized election. Keywords: political communication ethics, hoaxes, disinformation, 2024 election, media literacy, polarization, democracy integrity, information regulation, transparency, media literacy education. Abstrak Fenomena penyebaran hoaks dan disinformasi yang masif di berbagai platform media sosial telah menyebabkan polarisasi, menurunnya kepercayaan publik terhadap institusi politik, serta mengaburkan rasionalitas pemilih. Penelitian ini bertujuan untuk menganalisis praktik etika komunikasi politik selama masa kampanye Pemilu 2024, dengan fokus pada bagaimana aktor politik, media, dan masyarakat memproduksi serta merespons informasi yang berpotensi menyesatkan. Pendekatan kualitatif digunakan dengan metode studi literatur dan analisis wacana terhadap konten komunikasi politik di media daring. Hasil kajian menunjukkan bahwa lemahnya literasi digital, kepentingan elektoral jangka pendek, dan minimnya penegakan regulasi menjadi faktor utama yang memperburuk praktik komunikasi politik yang tidak etis. Oleh karena itu, diperlukan penguatan etika komunikasi politik melalui pendidikan literasi media, transparansi informasi dari lembaga penyelenggara pemilu, serta komitmen moral dari para pelaku politik untuk menjaga integritas demokrasi. Dampak dari komunikasi politik yang tidak beretika sangat signifikan, meliputi meningkatnya polarisasi sosial, menurunnya kepercayaan publik terhadap proses demokrasi, dan tergerusnya nilai-nilai moral dalam ruang publik. Untuk mengatasi hal tersebut, diperlukan penguatan etika komunikasi politik melalui pendidikan literasi media bagi masyarakat, penerapan regulasi yang tegas terhadap penyebaran informasi palsu, serta komitmen moral dari para aktor politik dan media massa untuk menjaga integritas demokrasi. Dengan demikian, etika komunikasi politik bukan hanya menjadi pedoman moral, tetapi juga instrumen penting dalam membangun Pemilu yang sehat, rasional, dan berkeadaban. Kata kunci: etika komunikasi politik, hoaks, disinformasi, Pemilu 2024, literasi media, polarisasi, integritas demokrasi, regulasi informasi, transparansi, pendidikan literasi media.